Probing Nanoscale Coassembly with Dual Mechanochromic Sensors. (18th January 2016) - Cingil, Hande E.; Boz, Emre B.; Wang, Junyou; Stuart, Martien A. Cohen; Sprakel, Joris
Abstract : Attractive electrostatic forces between polymers can be exploited to create well‐defined and responsive nanoscale structures. In the process of charge‐driven coassembly, the polymers involved undergo subtle conformational changes. However, ascertaining these conformational transitions, and relating this to the nanostructures that are formed, has remained elusive to date. Here it is shown how the force‐optical response of tailored mechanochromic polymers can be used to detect structural transitions that occur at the nanoscale during assembly. It is shown that at low‐charge stoichiometry, electrostatic binding causes individual macromolecules to stretch and stiffen. Remarkably, at stoichiometries close to full charge compensation a gradual transition from single molecular complexes to multimolecular micelles is observed. Moreover, the same macromolecular sensors reveal how the assembly pathways are fully reversible as the binding strength is weakened. These results highlight how mechanochromic polymer sensors can be used to detect the molecular transitions occur during supramolecular structure formation with high precision. Abstract : The force‐optical response of tailored mechanochromic polymers can be used to detect structural transitions that occur at the nanoscale during electrostatic coassembly. At low‐charge stoichiometry, electrostatic binding causes individual macromolecules to stretch and stiffen. As charge compensation is approached, these single molecule complexes condensate to form charge‐neutral multimolecular micelles.